THE EFFECT OF GUIDED INQUIRY LEARNING MODEL TO THE SCIENCE PROCESS SKILLS AND UNDERSTANDING THE CONCEPT OF PHYSICS - Adeline Silaban; Mariati P Simanjuntak (Jurnal Pendidikan Fisika, 2018)
This study aims to find out how the improvement of PPP and concept comprehension on students who are taught using guided inquiry learning model with conventional learning, whether the improvement of the KPS and the conceptual understanding of students using guided inquiry is better than conventional, whether the guided inquiry learning model influences the PPP and the students' understanding of the physics learning process and how the relationship between the students' KPS and the students' understanding of the concept. This research is a quasi experimental research with pretest-posttest experimental design group design design. The population is class X SMK Negeri 1 Stabat with a sample of two classes selected by random sampling. Data retrieval uses an instrument test of process science skills and concept comprehension. The results of the research for the increase of PPP of the two classes obtained pretest 42,13 and 42,86, while postes 79,66 and 55,06. The results of the research to increase the understanding of the concept of the two classes obtained pretes 40.83 and 33.33, while postes 79.00 and 58.83. The average yield of PPP increase using guided inquiry learning model is 0.64 and uses conventional learning 0.25. The mean improvement in conceptual understanding using guided inquiry learning model was obtained 0.68 and using conventional learning 0.38. The result of pearson correlation (r) is obtained> 0.05 ie 0.37.